Relativity, gravitation and cosmology a basic introduction - Cheng, Ta-Pei. (Oxford : Oxford University Press, 2010)
An introduction to Einstein's general theory of relativity, this work is structured so that interesting applications, such as gravitational lensing, black holes and cosmology, can be presented without the readers having to first learn the difficult mathematics of tensor calculus.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Relativity (Physics); Gravitation; Cosmology